Evaluation of the effect of direct-acting antiviral agents on melatonin level and lipid peroxidation in chronic hepatitis C patients - El-Mahdy, Nageh Ahmed; Abou-Saif, Sabry; Abd EL hamid, Medhat Ismail; Hashem, Heba M.; Hammad, Mohamed Anwar; Abu-Risha, Sally El-Sayed (Frontiers in Pharmacology, 2023)
Background: Oxidative stress and its end products, such as malondialdehyde (MDA) play a leading role in the pathogenesis of hepatitis C. Melatonin is a hormone that helps regulate circadian rhythms, which likely play a role in infectious diseases in terms of susceptibility, clinical expression, and outcome.Objective: The present study was conducted to assess serum malondialdehyde and melatonin levels in patients with chronic hepatitis C infection before and after the intake of direct-acting antivirals.Method: Forty hepatitis C patients were the subjects of this study. While ten healthy volunteers who matched in age and socioeconomic status served as the control subjects.Malondialdehyde and melatonin were assayed in the serum of the three groups, and the results were statistically analyzed.Results: Hepatitis C patients had significantly higher malondialdehyde (P<0.001) but significantly lower melatonin (P<0.001) as compared to the healthy controls. After 12 weeks of treatment with direct-acting antivirals, the malondialdehyde level decreased significantly (P<0.001) and the melatonin level increased significantly (P<0.001). A significant negative correlation between malondialdehyde and melatonin was observed.The present findings suggest that treatment of hepatitis C patients with Directacting antivirals improves liver function parameters and antioxidant profiles.